Regional health information exchange outside of the centralized national services for public health care in Finland: A national survey - Keränen, Niina; Tuovinen, Timo; Haverinen, Jari; Ruotanen, Ronja; Reponen, Jarmo (Finnish Journal of eHealth and eWelfare, 2022)
Health information exchange (HIE) is the mobilization of health care information electronically across organizations within a region, community, or hospital system. Nordic countries have been developing their health portals including national HIE services systematically. In Finland HIE begun with various regional health information exchange (RHIE) pilots in since 1998. The Kanta patient data repository component in the national HIE has been adopted in routine use since 2012. The current role of non-Kanta RHIE in relation to Kanta services is somewhat unclear. Our research questions are following: 1) Has the availability of RHIE services changed during 2017-2020? 2) What functional types of RHIE are there in Finland in 2020? 3) From the point of view of healthcare provider organizations, at what level is the availability to combine regional information seamlessly into the same view of local patient record systems? Data used in this study were collected using web-based questionnaires in 2017 and 2020 as part of the surveys for monitoring and assessment of social welfare and health care information system services in Finland. This study reported in this article covers all 21 public hospital districts and nearly all public primary health care centers. The quantitative data provided by the organizations were analyzed using SPSS software (version 25). The availability of a particular service or function was calculated as a percentage of all respondents in each sector. The results of this study show that the overall availability of RHIE services has not markedly changed 2017-2020. Functional types of RHIE meaning the role, use and types of RHIE in hospital districts in Finland varies greatly in 2020. We recognized three different types of non-Kanta RHIE in the non-combination organizations (one-way, symmetrical, full symmetrical). Seamless integration of at least some Kanta data into the same view as the main patient health record system data was more common than seamless integration of at least some non-Kanta regional data.